Pengaruh Media Video (Teman Sebaya) Terhadap Keterampilan Pemasangan Elektrocardiogram - Ramdani, Hasbi Taobah; Sulastini, Sulastini; Susyanti, Susan (Jurnal Keperawatan 'Aisyiyah, 2018)
The skill of installing an electrocardiogram (EKG) is one of the competencies that must be achieved by nursing students. To achieve these skills, it is necessary to have material delivery efforts by lecturers using the right media, so that the learning process becomes more effective. The learning process related to skills takes a lot of time and requires repetition until finally it is truly proficient. Therefore, it is necessary for media that are easily accessible at anytime and anywhere, one of which is through peer learning video media on ECG installation skills as a way to overcome skills problems in taking action on nursing students. The purpose of this study was to determine the effect of using video media (peers) on ECG installation skills in nursing students at STIKes Karsa Husada Garut. The research method is a quasi-experimental design with pre-post test group with control. The sampling technique used a total sampling of 104 students (intervention and control groups). The results of the study showed that some respondents had moderate skills in the installation of ECG before intervention. Most of the respondents have high skills in the installation of ECG after intervention. The results of bivariate analysis using the Whithney U Test Mann Test showed that there was a significant increase between ECG installation skills before and after the intervention was given in the form of using video media (peers) about the ECG installation skills (P Value = 0.000). The use of video media (peers) can improve the ability of nursing students in the action of EKG installation skills.